Investigation of the parameters influence of a cylindrical inductor with two-layer inwall on its temperaturePhysico-chemical prerequisites for decarburization of carbon-thermal reduction products Cr2O3 (Modern Problems of Metallurgy, 2022)
The development of physicochemical bases for solid-phase reduction of ore and man-made materials makes it possible to obtain spongy ligatures with specified properties. The use of such materials in metallurgy can significantly save mineral and energy resources. The thermodynamic analysis of the process of carbon-thermal reduction of chromium-containing raw materials to determine the conditions for obtaining an alloy with low carbon content. A six-factor mathematical planning experiment was performed using a half-replica of a complete factorial experiment. The analysis of solid-phase reduction of chromium-containing charge was carried out taking into account the following factors: temperature, time, gas phase composition, C/O, Cr/Fe and Fe/Ni ratios. A regression equation is obtained, which makes it possible to quantify the optimal value of each factor. By phase analysis of the Cr-O-C and Cr-Fe-O-C systems, the conditions that ensure the reduction of carbon in the final product are determined. The conditions for the appearance of metastable carbides are considered. Thermodynamic parameters that ensure the stability of solid phases are determined. Thermodynamic analysis with the participation of carbides in the process of solid-phase reduction was performed. Features of the carbido-thermal reduction mechanism are considered. The introduction of metallic iron into the charge creates the preconditions for the reduction of carbon, as well as intensifies the process of solid-phase reduction. The results of the performed researches testify to the fundamental possibility of complete reduction of Cr2O3 in the presence of iron rather quickly. The metallized product obtained under these conditions is largely susceptible to decarburization. Calculations show that at a ratio of Cr2O3 and carbon in the charge and an atomic ratio of Cr/Fe ≈ 1, the carbon content in the final product is ~ 4.5%. The charge mixture in principle allows to reduce the carbon concentration to ~ 2.8%. Replacing iron with iron oxides does not reduce the speed characteristics of the process. It should be noted that the replacement of Cr2O3 by natural material is accompanied by a significant reduction in the rate of recovery. The influence of some parameters on the speed characteristics of carbido-thermal reduction of chromium-containing materials is analyzed.
Keywords: chromium oxide; ligature; solid-phase reduction; carbide; factor analysis